GENERALISASI FUNGSI GENAP PADA SISTEM KOORDINAT KUTUB DAN BEBERAPA SIFATNYA - Firdaus Ubaidillah (UNEJ e-Proceeding, 2022)
The function r is said to be an even function if for every in R. In the polar coordinate system, the graph of the even function is symmetric about the polar axis, i.e., the line , but not vice versa. In this paper, we will introduce a more general definition of an even function, or generalized even functions, in a polar coordinate system, which is given the function and for a in R then for every in R. In addition, some properties of the generalized even functions to the polar coordinate system will be discussed. Keywords: even function, symmetric graph, polar coordinate system